THE QUR’ANIC LEARNING SOFTWARE IN DIGITAL ERA: A THREAT TOWARDS THE VALUE OF QUR’ANIC ORTODOXY IN INDONESIA - Hamdi Putra Ahmad (Nazharat: Jurnal Kebudayaan, 2021)
The gadget’s software applications nowadays appear to be highly popular and its use has been elevating among gadget users. This kind of technological advance also touched the Qur’anic learning process in Indonesia. On the one hand, not only does the emergence of Qur’anic learning software stimulate children’s interest, but it also provides a lot of features that will make children quickly understand and practice the Qur’anic reciting. On the other hand, this kind of learning method can threat the value of Qur’anic orthodoxy which had been applied among traditional Muslim societies since the emergence of Islam in Indonesia. Some resources have noted that there were some sacred values and courtesies perpetuated by traditional Muslims while teaching Qur’anic reciting. This article will track the historical journey of Qur’anic learnings in Indonesia and discuss how the emergence of Qur’anic Learning software (as the logical consequence of technological improvement) can threat the existence of some ancient orthodoxies toward the Qur’an.